Антиоксидантна активність біологічно активних речовин деревних плодових ліан - Skrypchenko, N.V.; Levon, V.F. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2016)
The evaluation of the antioxidant activity of biologically active substances (BAS) of vegetative and generative organs of woody fruit vines of Actinidia L., Schisandra Michx. and Vitis L. genus, introduced in Right Forest-Steppe of Ukraine, is given. The fruits and leaves of plants are a very valuable source of BAS, their total antioxidant activity ranges from 0.3 to 1.6 mg/ml and depends on the species and variety of plants, as well as the phase of their growth. The leaves of woody vines have much higher antioxidant activity compared to fruits. The highest antioxidant activity was found for S. chinensis leaves. It was found, that Actinidia fruits with more intensive purpur color have the highest antioxidant activity of BAS, which is due, primarily, by the presence of anthocyanins.